Automated Design of Space Trusses - Weaver, Jr.; Patton, Fredrick W. (Engineering Journal, 1968)
The design by the elastic theory of a complex framed structure consists of the selection of an initial configuration followed by cyclic revisions. In each design cycle the structure is analyzed for predicted service loads and evaluated according to specified stress criteria. Then the structure is modified and the process repeated until a satisfactory design is obtained. The task of computer programming for structural design involves certain considerations not encountered in analysis. Engineering decisions relating to geometry, load systems, types of members, support conditions, stress criteria, and methods of connection cannot be directly incorporated into a computer program. However, if these decisions are made beforehand and are reflected in the input data, an iterative procedure of analysis and revision can be programmed to produce convergence to a suitable design. The role played by the computer in the design process may vary considerably. If the designer intervenes in each cycle, inspects the results, makes decisions, and alters parameters in accordance with his decisions, the operation is said to be "computer-aided design." On the other hand, if all parameters are predetermined and the computer is allowed to iterate to a final selection of member sizes without human intervention, the term "automated design" applies. This paper deals with the latter technique for the design of structures framed as space trusses.